Quantifier Spreading Errors during Pronoun Processing in Aphasia - Seçkin Arslan; Gamze Yeşilli Puzella; Semra Selvi Balo; Özgür Aydın; İlknur Maviş (Psikoloji Çalışmaları)
Aphasia is an acquired language disorder that impacts all language abilities, rendering normal communication extremely difficult. Grammatical processing is often impaired in aphasia. Pronouns are often found to be effortful, with difficulty interpreting to whom a pronoun might refer. This study aimed to investigate whether interpreting pronouns and reflexives with and without potential quantified antecedents (i.e., “Every rabbit / Rabbit is pointing at itself/it/monkey”) are impaired in aphasia in Turkish, and whether quantifier spreading errors occur during pronoun/reflexive processing. A total of 12 people with aphasia (PWA) (two females, Mage= 59.7, SD = 14.55) and 15 age-matched healthy controls were recruited and asked to listen to 24 sentences in conditions of non-quantified and quantified subjects in which different referential and pronominal variables were controlled for (pronoun, reflexive, and R-expression). These participants were admitted to a picture-sentence matching paradigm with an end-of-trial truth-value judgment task. They were presented with a picture which either matched or mismatched the sentence contexts, and they were asked to respond. Their accuracy and response times were recorded and analyzed using mixed-effects regression models. The findings showed that the PWA performed more poorly and slowly than the control group and that both the groups performed more slowly responding to the quantified subjects than non-quantified ones. The PWA made interpretation errors in mismatch conditions, particularly for quantified subjects, evoking longer response times compared to non-quantified subjects. In conclusion, this study showed that quantifier spreading errors are observed in Turkish aphasia, which does not necessarily depend on pronominal/anaphoric resolution. It is suggested that the PWA’s sentence interpretation difficulty was underlined in two forms of separate impairments: interpreting quantifier scope and impairments in resolving pronominal/anaphoric elements.